A 15-year-old boy with travel-imported dengue haemorrhagic fever - Anna Tomasik; Maria Pokorska-Śpiewak; Barbara Kowalik-Mikołajewska; Magdalena Marczyńska (Termedia Publishing House, 2022)
Dengue is a viral, mosquito-spread disease with a high prevalence in tropical and subtropical areas. We report a case of travel-imported dengue haemorrhagic fever in a 15-year-old Polish boy. The patient presented with fever, headache, and muscle pain. He was initially diagnosed with influenza. He gradually developed skin rash, mild hepatosplenomegaly, episodic gingival bleeding, and mild symptoms of plasma leakage in the form of palms swelling. The laboratory results revealed leukopaenia and thrombocytopaenia with increasing haematocrit. Dengue virus infection was confirmed by simultaneous detection of NS1, IgM, and IgG antibodies. The patient was treated empirically in the critical phase with satisfactory outcome. The symptoms subsided and the platelet and leukocyte levels gradually reached the normal range for his age.